Real-world Patient-reported Rates of Non-severe Hypoglycaemic Events in Germany - Kulzer, B.; Seitz, L.; Kern, W. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Hypoglycaemia is a common side effect of insulin therapy in diabetes patients, with negative physical and emotional impacts. Despite this, there are few studies investigating the frequency of non-severe hypoglycaemic events from the perspective of patients in the real-world setting. We investigated self-reported NSHE frequency and levels of hypoglycaemia awareness in Germany.Respondents>15 years with Type 1 or insulin-treated Type 2 diabetes (receiving basal only, basal-bolus or other insulin regimens) were recruited using online panels to complete≤4 questionnaires. Questionnaires collected demographics, non-severe hypoglycaemic event rates and patient-reported level of hypoglycaemia awareness. Non-severe hypoglycaemic event rates are reported as respondent-week records and calculated using data from all respondents completing at least one questionnaire.A total of 1 771 respondent-week records were obtained from 614 participants. Mean non-severe hypoglycaemic event rates per respondent-week were 1.6 for Type 1 and 0.6–0.8 for Type 2, with estimated annual rates of 83 and 31–42 respectively. Two-thirds of Type 1 (65%) and Type 2 (61–72%) respondents reported impaired levels of awareness or unawareness of hypoglycaemic events (inability or impaired ability to recognise the symptoms of hypoglycaemia). Respondents’ self-reported hypoglycaemia-awareness was significantly associated with the proportion of asymptomatic non-severe hypoglycaemic events; respondents classified as being unaware of hypoglycaemia had a higher proportion of asymptomatic non-severe hypoglycaemic events than aware respondents.Non-severe hypoglycaemic events are common in people with Type 1 or insulin-treated Type 2 diabetes in the real-world setting in Germany but may still be underestimated due to an inability to recognise the symptoms of hypoglycaemia.
Keywords: hypoglycaemia; insulin therapy; diabetes-related distress; hypoglycaemia awareness